Non-Pharmacology Pain Management on Neonate: A Systematic Review - Reni Ilmiasih; Yuni Sufyanti Arief; Henik Tri Rahayu (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
ntroduction: Neonates undergoing treatment often experience pain and painful procedures. Proper pain management needs to be done considering various cases in neonates with different pain experiences and causes. This study aimed to review the effect of non-pharmacological pain interventions on neonates. Methods: A systematic review was conducted to investigate the effect of non-pharmacology pain management in neonates. Studies were obtained from Proquest, Clinical Key for Nursing, Science Direct, and EBSCO databases. This study was limited to Randomized Control Trial studies published between 2015 and 2022, using subject headings and synonyms as keywords: neonate, neonatal, newborn, pain management, non-pharmacology pain management, and pain level. Next, JBI (Joanna Brings Institute) was used to evaluate journal quality, and thematic analysis was used as the data analysis method. Results: The search identified 659 relevant studies, and 19 studies have met the criteria. Nineteen articles show that various effective non-pharmacological pain management in premature and term infants are a sweet solution, skin stimulation, positioning, audio stimulation, and olfactory stimulation. Twelve journals discuss comparisons between interventions, and six journals discuss positions like facilitated tacking, hammock, swaddling, holding, and nesting. Five journals discuss combined pain management. Most of the journals (12 journals) discuss breastmilk odor stimulation and breastfeeding. The study also proved that multiple pain management was more effective than one type of intervention. Conclusion: The case-tailored practice of pain management in neonates and selecting the right combination of pain management will help reduce pain and increase comfort.